The impact of COVID-19 pandemic on child development: systematic review - Kaur, Ravneet; Dahiya, Dipsha (International Journal of Contemporary Pediatrics, 2023)
The Coronavirus disease 2019 (COVID-19), emerged as a global health issue in December 2019 which lead to the sudden implementation of social distancing norms worldwide, including school closures. This stress scenario can alter physical activity and sleep, which are shown to have a profound impact on brain plasticity. The PubMed, Europe PMC, Google Scholar and Science Direct database was searched between July 1st 2022 and September 20th 2022. The inclusion criteria was a) articles in English, b) Articles with study population as children and the exclusion criteria was a) Articles whose full text couldn’t be obtained, b) journals not accessible online. After thorough analysis of 2371 records and removing the studies following the exclusion criteria, a total of 7 studies were included in this review. The results of these studies were tabulated. Among the 4.4 million COVID-19 deaths reported in the MPIDR COVerAGE database, 0.4% occurred in children and adolescents under 20 years of age. Expectant mothers were reluctant to attend clinics and were delayed in seeking treatment, due to the fear of being exposed to the virus. Maternal stress is thought to affect early structures of the developing limbic system. These can be potentially related factors and causes of neuropsychiatric disorders in children. Due to the protracted lockdown’s impact on the economy, food shortages and an increase in food prices resulted in children not receiving the required nutrients. Before being confined to the home, toddlers had more opportunity to advance their motor development at a more complex level while acquiring more communication structures. Information about the impact of lockdown due to an epidemic on motor development of children is relevant to policy makers to aid them in developing strategies to help children cope with epidemic/pandemic-driven adversity and ensure their healthy development.